Religious symbolism and politics: hijab and resistance in Palestine. Issue 6 (3rd May 2021) - Alayan, Samira; Shehadeh, Lana
ABSTRACT: The covering of Muslim women has become a topic of contention on a global level. Relying on in-depth interviews in the Palestinian territories, our study illustrates the motivation to wear hijab under a colonial context and compares the justifications women give for wearing the hijab under two different types of political subjugation. Palestinian Muslim women in both the West Bank and East Jerusalem, frequently provided political justification for wearing the hijab. In the West Bank, where interactions with the occupier are limited to tense encounters with soldiers, they use the hijab as a defiant symbol against the Israeli occupation. In East Jerusalem, Palestinian women use the hijab as a visible representation of their identity and resilience, but at the same time they are more cautious and consider the way the hijab might be viewed by Jewish-Israeli civilians, whom they encounter on a daily basis.